(untitled) (Ciencia Veterinaria, 2017)
The current work analized ofthe pH variation, at the level ofthe 12a dorsal vertebra for the U. E., 9 a dorsal vertebra for Kosher cuts and a1l the diferent cuts (nine at total) obteiled from the front quaters bovines. For determination were used cooled quaters of bovines, convention Israel - Argentina (7º in 24 Hs.) and back quartes naturated in traditional form (24 at 48 Hs. at the temperature 01’ carnera between 2 ºC and 4ºC). It was determinated the pH in the cuts after the entrance to despostes and sukequently at find rinse, they were not observed variations at the values obteined, It wasrnade several determinations for aplications atatistic methods to many samples , normal distribution (Gauss). They were observed pH variation from cooled cuts (Israel) and maturated cuts (U. E.) near 0,3 upl l. In someone cuts the pH is not constant , there observed the flexor muscles in shin, neck and shank base a greater pH., (more than 6 upIl); the congelation and descongelation no make variations. As the result of pH in not constant in every cuts, the defference deppend al the considerated muscle very important in shin, neck and shank were the flexors musele in accord depending of the acnviry and or relation between conectiv tissue, the ph medition were not minor at 6 uph, independently of cooled or maduration procedures